Spiritually oriented interventions for counseling and psychotherapy - Aten, Jamie D.; McMinn, Mark R.; Worthington, Everett L. , 1946- (American Psychological Association, 2011)
"Spirituality and religion influence the way many clients interpret their life experiences. Recognizing this reality, Spiritually Oriented Interventions for Counseling and Psychotherapy offers mental health professionals an in-depth look at how to integrate both Western and Eastern spiritually oriented interventions into clinical practice.Through a series of carefully selected interventions, the book examines in detail how each can be utilized in an ethically and culturally sensitive manner with a diverse spectrum of clients who wish to address sacred themes in therapy.Each chapter presents practical strategies and clinical examples of how to successfully implement spiritually oriented interventions into treatment. Relevant theories and research findings are also included.This book will be a valuable tool for equipping mental health professionals to work with spiritually and religiously diverse clients."